Tissue‐resident CXCR4+ macrophage as a poor prognosis signature promotes pancreatic ductal adenocarcinoma progression. Issue 11 (21st February 2023) - Liao, Zhenyu; Ye, Longyun; Li, Tianjiao; Jin, Xing; Lin, Xuan; Fei, Qinglin; Zhang, Huiru; Shi, Saimeng; Yu, Xianjun; Jin, Kaizhou; Wu, Weiding
Abstract: Macrophage is an essential part of the tumor immune microenvironment of pancreatic ductal adenocarcinoma. In our study, we explored the CXCR4 + macrophages subset on its prognosis value, immune profile and distinct function in pancreatic cancer progression. Specimens from 102 postoperative pancreatic patients were analyzed by flow cytometry or immune‐fluorescence, and the prognostic value of CXCR4 + macrophages infiltration was further determined by Cox regression. In silico analysis on TCGA, ICGC database and single‐cell sequencing of pancreatic ductal adenocarcinoma further validated our findings. We found that high CXCR4 + macrophages infiltration was associated with poor overall survival ( P < .01) and disease‐free survival ( P < .05) as an independent factor. CXCR4 + macrophages exhibited an M2 protumor phenotype with high expression of CD206. The function of CXCR4 + macrophages was further analyzed in the murine orthotopic PDAC model with its tumor promotion effect and inhibition of CD8 + T cells. Mechanistic and RNA‐seq analysis showed that CXCR4 + macrophages participated in extracellular matrix remodeling procedures and especially secreted SPARC through CXCR4/PI3K/Akt pathway promoting tumor proliferation and migration. Our study reveals that CXCR4 + macrophages infiltration is an indicator of poor prognosis of PDAC and targeting these cells was potentially crucial in immunotherapy of PDAC. Abstract : What's new? Tumor‐associated macrophages are known to influence the progression of pancreatic ductal adenocarcinoma (PDAC). The utility of macrophages in prognostic assessment of PDAC, however, remains unclear. In our study, macrophages with high expression of C‐X‐C chemokine receptor type 4 (CXCR4 + ) were investigated to determine their immune profile, function and prognostic value in PDAC. Analyses reveal that CXCR4 + macrophages are significantly increased in PDAC. In animal models, CXCR4 + macrophages exhibited an immunosuppressive M2‐phenotype, an ability to self‐proliferate and promoted tumor proliferation and migration. In human patients, high infiltration of CXCR4 + macrophages independently predicted poor surgical outcome and poor overall survival.